BEaTS-β: an open-source electromechanical bioreactor for simulating human cardiac disease conditions - Takaya, Hiroki; Comtois-Bona, Maxime; Spasojevic, Ana; Cortes, David; Variola, Fabio; Liang, Wenbin; Ruel, Marc; Suuronen, Erik J.; Alarcon, Emilio I. (Frontiers in Bioengineering and Biotechnology, 2023)
Heart disease remains the leading cause of worldwide mortality. Although the last decades have broadened our understanding of the biology behind the pathologies of heart disease, ex vivo systems capable of mimicking disease progression and abnormal heart function using human cells remain elusive. In this contribution, an open-access electromechanical system (BEaTS-β) capable of mimicking the environment of cardiac disease is reported. BEaTS-β was designed using computer-aided modeling to combine tunable electrical stimulation and mechanical deformation of cells cultured on a flexible elastomer. To recapitulate the clinical scenario of a heart attack more closely, in designing BEaTS-β we considered a device capable to operate under hypoxic conditions. We tested human induced pluripotent stem cell-derived cardiomyocytes, fibroblasts, and coronary artery endothelial cells in our simulated myocardial infarction environment. Our results indicate that, under simulated myocardium infarction, there was a decrease in maturation of cardiomyocytes, and reduced survival of fibroblasts and coronary artery endothelial cells. The open access nature of BEaTS-β will allow for other investigators to use this platform to investigate cardiac cell biology or drug therapeutic efficacy in vitro under conditions that simulate arrhythmia and/or myocardial infarction.